Evolution of the structure and dynamics of bovine serum albumin induced by thermal denaturation. Issue 33 (11th August 2020) - Matsarskaia, Olga; Bühl, Lena; Beck, Christian; Grimaldo, Marco; Schweins, Ralf; Zhang, Fajun; Seydel, Tilo; Schreiber, Frank; Roosen-Runge, Felix
Abstract : Using small-angle and time-resolved quasielastic neutron scattering, we study the process of thermal denaturation in concentrated protein solutions, and obtain structural and dynamical signatures of partial unfolding and subsequent cross-linking. Abstract : Protein denaturation in concentrated solutions consists of the unfolding of the native protein structure, and subsequent cross-linking into clusters or gel networks. While the kinetic evolution of structure has been studied for some cases, the underlying microscopic dynamics of proteins has so far been neglected. However, protein dynamics is essential to understand the specific nature of assembly processes, such as diffusion-limited growth, or vitrification of dense liquids. Here, we present a study on thermal denaturation of concentrated solutions of bovine serum albumin (BSA) in D2 O with and without NaCl. Using small-angle scattering, we provide information on structure before, during and after denaturation. Using quasi-elastic neutron scattering, we monitor in real-time the microscopic dynamics and dynamical confinement throughout the entire denaturation process covering protein unfolding and cross-linking. After denaturation, the protein dynamics is slowed down in salty solutions compared to those in pure water, while the stability and dynamics of the native solution appears unaffected by salt. The approach presented here opens opportunities to link microscopic dynamics to emerging structural properties, with implications for assembly processes in soft and biological matter.